Idea občana – válečníka a „moderní“ maskulinní identita: modelová studie z dějin Spojených států - Jiří Hutečka (Theatrum Historiae)
Only in recent years it became usual to cross (cautiously indeed) borders between gender history and military history, and in Czech historiography particularly, this kind of border-crossing is still virtually non-existent. Although it is not very surprising considering the “state of the art” in both fields here, it must be surprising in any other way, because there is a hardly any more “gendered” human endeavor than warfare – a fact generally acknowledged by theorists and thinkers from Bourdieu to Virginia Woolfe. This article is an effort to present a case study of connection between these two fields. The US Civil War is a great case study for this effort as it was a war of volunteers – most soldiers served in the ranks not because of direct conscription (only low percentage were actual draftees) or because of economic pressures (although that was not uncommon). They mostly served to fulfill what we can call the “citizen-warrior” concept as borrowed by contemporary theorists from ancient republics. The “warrior image” was at the very core of their understanding of their own masculinity, as was widely recognized not only by themselves (various sources as diaries, memoirs and literature are used here), but also by the society at large, and especially by women, who sometimes consciously, sometimes not were putting an immense pressure on men to “be men”. This pressure from home community had, thanks to the local character of regiments in both armies and thanks to the “crowded” character of battlefield, an overwhelming tactical implications – the field of battle became the ultimate expression of Bourdieu’s “masculine space” – outward, official, public, short, dangerous, spectacular. And, thanks to general literacy, a closely watched one indeed. The principle of mutual support and/or control thus played an important part in men’s courage. The “citizen-warrior” principle had yet another important implication – a strategic one. At the end, it led to what is called here a “gender strategy” of the Union army in 1864– 1865 campaigns. For sure, these campaigns were not primarily set in motion because of some innovative “gender thinking” – target of Grant’s “raids” was, above all, Confederate logistics. But the “gender strategy” came as a secondary result, as is widely accepted by authors like Reid Mitchell. What is even more interesting for us here is the fact that Union authorities (Sherman, Halleck, and many other officers) were completely conscious of its effects on the “masculine side” of Confederate morale – i.e., of pushing a wedge between the military (soldier) and warrior (defender) role of southern men. What resulted was a massive desertion rate from the Confederate Army in late 1864 and early 1865 (danger to their families being one of the most important, although not sole reason for soldier’s leaving the front). This represents not only interesting insight into contemporary thinking, but, somewhat more importantly, yet another example that modern civic society, as established in 19th century, is only a little more sophisticated incarnation of traditional warrior society.